Contrasting impacts of climate change on connectivity and larval recruitment to estuarine nursery areas. (August 2021) - Cabral, Henrique; Drouineau, Hilaire; Teles-Machado, Ana; Pierre, Maud; Lepage, Mario; Lobry, Jérémy; Reis-Santos, Patrick; Tanner, Susanne E.
Highlights: Simulation of fish larval dispersal from coastal spawning areas to estuaries. Analysis of 4 species over 20 years (1989–2008) along the Western Iberian coast. High intra- and interannual variability in larval dispersal and recruitment. Average recruitment estimated between 1.7% and 7.3% of released larvae. Recruitment and connectivity patterns differed in "cold" and "warm" year archetypes. Higher recruitment and larval transport in "warm" years for three out of four species. Abstract: Connectivity between spawning grounds and recruitment areas of marine fish species drives population structure and dynamics, and may be affected by climate-induced changes in oceanographic processes. We analysed the variability in recruitment success of larvae to estuarine nursery areas along the Iberian Atlantic coast of four fish species with distinct spawning grounds and periods ( Solea solea, Solea senegalensis, Platichthys flesus and Dicentrarchus labrax ). Concomitantly, we explored the variations in connectivity patterns between "cold" and "warm" year archetypes. We used a three-dimensional Lagrangian transport particle-tracking model integrating time series of velocity, temperature and salinity fields archived from the Regional Ocean Modelling System. We simulated individual larval dispersal, over extended spawning periods, from multiple coastal spawning areas to estuarine recruitment areas over 20 years (1989–2008). Overall, high inter- and intra-annual variation were found for all species. Nonetheless, highest overall average recruitment estimates were obtained for S. solea and D. labrax (with 7.3% and 5.7% of the particles released in spawning areas reaching a recruitment area, respectively) compared to S. senegalensis and P. flesus (3.4% and 1.7%, respectively). Recruitment estimates were overall higher at earlier spawning dates but peak values occurred at later spawning events. Regarding spawning origin, particles that recruited to the northern part of the Iberian coast were mainly from southern source areas. For estuarine systems located in southern Portugal, the relative contributions of northern and southern coastal spawning areas were more balanced, or with a preponderance of northern spawning areas (namely for S. senegalensis and D. labrax ). Recruitment was higher in "warm" years compared to "cold" years, except for P. flesus for which nil recruitment was registered in the southern Iberian coast during "warm" years. Larvae also travelled farther in "warm" years compared to "cold" years. Ultimately, understanding how oceanographic conditions govern larval recruitment to estuarine nursery areas is pivotal to forecast the potential impacts of climate change on species with segregated life histories, and will underpin long term management and safeguarding of estuarine nursery role.